Learning innovations in training activities: A systematic literature review - Arsyil Waritsman; Irma Djanapa Bulow (Balai Diklat Keagamaan Ambon, 2022)
This study aims to describe the innovations that have been applied in learning in training activities and describe the impact of the application of learning innovations on training activities. The method used in this study is a Systematic Literature Review. Data collection is carried out by documenting and reviewing articles either in national journals or proceedings of national seminars related to learning innovations applied to training and articles related to the impact of learning innovations in the period 2012 to 2021. The data were analyzed using a qualitative descriptive approach by going through four stages, namely data collection, data reduction, data presentation, and conclusion drawing. The findings show that the learning innovations applied to training are in the form of the application of e-learning, open design training models, interactive training methods, the use of learning media with the help of canva, the creation of video-based learning media, innovations in the training curriculum, and the implementation of blended learning in training activities by utilizing the use of the application and web-based information technology such as zoom, moodle-based learning management system (LMS) and google meetings. Then, information was also obtained that the impact of the application of learning innovations included the improvement of human resource professionals, increasing the performance of human resources, and the formation of active and creative human resources at work.